Design of subsidized fertilizer prediction information system with safety stock methodology. Issue 5 (March 2021) - Setiawan, R; Rahayu, S; Nugraha, G G S; Baswardono, W; Satria, E
Abstract: The purpose of this research is to design a subsidized fertilizer information system equipped with a prediction system with a safety stock method. This study uses the waterfall methodology with stages of Analysis, Design, Coding, and Testing, as well as the safety stock method for prediction. By testing using black-box testing with system modeling using the Unified Modelling Language (UML) and Business Process Model and Notation (BPMN). The results of this research are a prototype of a fertilizer information system for data collection activities, fertilizer expenditure from the warehouse, and fertilizer orders based on predictions. This research takes a case study at PT. Anugerah Ihsan Makmur, which is a company engaged in the distribution of subsidized fertilizers in the Garut region. This information system can help record the distribution of fertilizer, determine the amount of fertilizer procurement that must be ordered to suppliers to meet inventory needs so that there are no shortages, and can use as a management report on the distribution of subsidized fertilizers to the government.